Hysteroscopic outpatient metroplasty to expand dysmorphic uteri (HOME-DU technique): a pilot study. Issue 2 (February 2015) - Di Spiezio Sardo, A.; Florio, P.; Nazzaro, G.; Spinelli, M.; Paladini, D.; Di Carlo, C.; Nappi, C.
Highlights A novel hysteroscopic technique for metroplasty, the "Hysteroscopic Outpatient Metroplasty to Expand Dysmorphic Uteri (HOME-DU technique)" was evaluated. The study was conducted on 30 infertile women with dysmorphic uterus (T-shaped and tubular-shaped/infantilis uteri) – as diagnosed by office hysteroscopy and three-dimensional trans-vaginal ultrasound – who underwent the HOME-DU technique. Our data seem to support the safety and efficacy of such outpatient technique in order to improve the volume and shape of dysmorphic uteri. The improvement of the uterine cavity volume and morphology may offer new approaches in increasing reproductive outcomes.